[Book Review] Ian Loader and Richard Sparks, "Public Criminology?" London: Routledge, 2010 - Copson, Lynne (2015)
Written during a period of burgeoning interest in normative questions about the public role(s) and function(s) of social scientific research in the 21st century, Public Criminology? by Ian Loader and Richard Sparks presents a welcome contribution to contemporary debates concerning the possible and desirable interactions between academic knowledge and public engagement (including discussions of what is entailed by the latter term in the first place), focusing specifically on the production, consumption of criminological knowledge in a contemporary context